2020
DOI: 10.3390/ijerph17124399
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Family Planning Use in Mali and Senegal

Abstract: The total fertility rate in Mali (6.2) is the third highest in the world. Despite sociocultural similarities, the total fertility rate in neighboring Senegal is 4.2. The aim of this study is to identify factors which may help to explain the differences between the two countries and which may thereby inform family planning policy in Mali. A cross-sectional study was conducted with a convenience sample of 602 married women aged 16–50 from urban and rural sites in southern Mali and Senegal. A total of 298 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
0
22
1
2
Order By: Relevance
“…Married women who were sterilized and declared as infecund were excluded from the analysis. Several individual and community-level explanatory variables were chosen based on prior evidence [ 6 , 14 16 , 18 , 19 , 36 , 47 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Married women who were sterilized and declared as infecund were excluded from the analysis. Several individual and community-level explanatory variables were chosen based on prior evidence [ 6 , 14 16 , 18 , 19 , 36 , 47 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Senegal, despite the low contraceptive utilization, few studies have focused on factors associated with the low contraceptive usage [13,17,[34][35][36]. Moreover, available studies on utilization of contraceptivs were either based on the 2012/13 DHS [35] and 1992-2013/14 DHS data [13], focused on single factor [13,34] and limited to a single study area [34,36]. None of these studies have examined the association between individual and community-level factors and utilization of contraceptives in Senegal.…”
Section: Introductionmentioning
confidence: 99%
“… 19 For example, some research has shown that opposition from others, including spouses, mothers-in-law, or providers and community members may influence women’s, men’s, and couple’s family planning decisions. 17 , 20 24 A couple-level analysis from Ethiopia found that husband’s opinions about contraception and childbearing carried more weight than the opinions of his female partner. 25 In the 2018 Senegal Demographic and Health Survey, men in union reported a higher ideal number of children (8.0) on average than women in union (5.9), 26 and a husband’s higher ideal number of children may influence his wife’s decisions to use (or not use) contraception.…”
Section: Introductionmentioning
confidence: 99%
“… 25 In the 2018 Senegal Demographic and Health Survey, men in union reported a higher ideal number of children (8.0) on average than women in union (5.9), 26 and a husband’s higher ideal number of children may influence his wife’s decisions to use (or not use) contraception. 20 Social norms may also limit contraceptive use: in a recent study in Senegal, 25% of women believed that their religion (primarily Islam) prohibited family planning use. 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation